(untitled) (The South East European Journal of Economics and Business, 2026)
As efforts to achieve global sustainability goals intensify, it is increasingly important to understand the environmental consequences of countries’ economic policies, particularly the impact of macroeconomic variables such as external debt. This study analyses the impact of Türkiye’s external debt on environmental sustainability for 1970–2023 using the Fractional Frequency Fourier Autoregressive Distributed Lag (FFF-ARDL) method. Moreover, the variables of economic growth, renewable energy consumption (REN), and non-renewable energy (NREN) consumption were included in the model, and the Environmental Kuznets Curve (EKC) hypothesis was tested. Carbon dioxide (CO2) emissions were used as a proxy for environmental sustainability. The long-run coefficient findings indicate that increases in external debt reduce CO2 emissions, while economic growth initially increases emissions but then declines after a certain income threshold, confirming the EKC hypothesis. Moreover, REN energy consumption decreases CO2 emissions, whereas NREN energy consumption increases them. The Fourier Toda-Yamamoto test results indicate unidirectional causality running from CO2 emissions, REN, and external debt to NREN consumption. There is also unidirectional causality running from economic growth, REN, and NREN consumption to external debt. These findings suggest that Türkiye’s external debt management and the transition toward REN sources are crucial for reducing CO2 emissions.